The Concept of Humility according to St. Isaac the Syrian: Adoption, Perfection, and Repentance - Hendi Hendi; Sarah Apriliana (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
The virtue of humility, as espoused by both Old Testament prophets and Jesus in the New Testament, is not merely a commendable personal quality; rather, it can be experienced as a profound spiritual state. St. Isaac the Syrian articulates three key concepts of humility that elucidate its connection to spiritual experience, which are applicable to both laypersons and church leaders. Firstly, humility enables the individual to be adopted by God as His child, thereby suggesting that humans, through humility, can participate in the divine nature when united with God in eternity. Secondly, humility functions as a conduit for the perfection of the soul. Those who achieve spiritual perfection do so through the virtue of humility, which shapes their attitude towards worldly pleasures and desires, aligning them more closely with the love of God and the pursuit of eternal values. Finally, humility is a crucial element in the process of repentance. Genuine repentance, characterised by the acknowledgement and remorse of one's sins, is grounded in humility. This humility cultivates a profound sense of gratitude for God's grace and mercy, enabling individuals to recognise their vulnerabilities and seek divine guidance. Consequently, humility not only facilitates personal spiritual growth but also reinforces one's relationship with God.